The influence of work motivation and compensation on employee performance in Mandiri Pematangsiantar CU - Hadi Panjaitan; Jopinus Saragih; Hendri Mayanta Tarigan; Nanda Rianty Pardede; Ruth Valentina Br Sembiring (Institute of Computer Science (IOCS), 2022)
This study aims to determine and test the effect of the variables Work Motivation and Compensation on Employee Performance at the Mandiri Pematangsiantar CU. And the data used in the study The population used in this study were CU employees. Primary data were Mandin Pematangsiantar with a sample size of 45 respondents. The data analysis technique used is multiple linear regression analysis which aims to calculate the magnitude of the regression coefficient to show the magnitude of the influence of the variables Work Motivation and Compensation on Employee Performance. While the model feasibility test shows that the variables Work Motivation and Compensation together have a significant effect on employee performance at the Mandiri Pematangsiantar CU. . Meanwhile, the results of the partial determination coefficient test (2) show that compensation is the variable that has the dominant influence on employee performance at Mandiri Pematangsiantar CU.